Juridical Implications of Constitutional Court Decision Number 105/PUU-XXII/2024 Regarding Freedom of Expression in the Digital Space - Chariansyah, Hery (SIGn Jurnal Hukum, 2025)
Constitutional Court Decision Number 105/PUU-XXII/2024 emerges as a crucial judicial intervention amid an Indonesian digital legal landscape characterized by the widespread criminalization of freedom of expression through vaguely worded articles in Law Number 11 of 2008 and its amendments. This research aims to comprehensively analyze the juridical implications of this decision, evaluate its consistency with constitutional norms and international human rights standards, and map its implementation challenges and prospects for future legal reform. Utilizing a normative legal research method that integrates statute, case, and comparative approaches, this study deeply dissects the legal reasoning (ratio decidendi) of the Constitutional Court and its impact on the legal system. The findings indicate that this decision fundamentally transforms the crime of defamation into an absolute complaint-based offense that purely protects individual honor. It significantly strengthens legal protection for public criticism and the democratic oversight function of citizens. It was also found that the decision is fully aligned with the constitutional guarantees in the 1945 Constitution and consistent with the principles of necessity and proportionality within the ICCPR. It is concluded that although the ruling represents a monumental advancement, its implementation faces serious challenges. These challenges include a legal vacuum concerning the protection of institutional reputation and the urgent need for a cultural shift within law enforcement agencies, thereby necessitating that this decision be leveraged as momentum for a broader digital law reform agenda.